Tradución e edición educativa non universitaria en Galicia - Valado, Liliana (Madrygal. Revista de Estudios Gallegos, 2008)
The author analyses the Galician business of edition, exploring the relevant position that translation symbolises as we afirm our identity concerning the so-called libro galego (“Galician book”) when referring it as an industry. Therefore we focus on the realm of the written textbooks for non-university education and their translation into Galician language, but we also study briefly some other types of written texts which are important for the History of translation in Galicia. For that reason, we aim at showing that those written materials for education which were translated and edited are characterized by the same quality level as those ones which are written by Galician authors, in case the accurate process of translation is included.